Blood concentration of β-hydroxybutyrate in Jersey and Holstein herds under grazing and its association with productive, reproductive and health indicators - Saborío-Montero, Alejandro (2016)
Blood concentration of β-hydroxybutyrate in Jersey and Holstein herds under grazing and its association with productive, reproductive and health indicators. The blood concentration of β-hydroxybutyrate (βHBA) in 2 high yielding cow herds, one of Jersey breed and the other Holstein, was correlated with productive, reproductive and health indicators. The Jersey herd was grazing in Oreamuno and the Holstein in La Union, both in Cartago, Costa Rica, and including primiparous and multiparous cows. Blood samples were taken from coccygeal vessels of 117 and 114 Jersey cows at 8±3 and 30±3 days of lactation (DL), and from 72 and 50 Holstein cows at 5±3 and 30±3 DL, respectively; concentration of βHBA was analyzed in situ and the herd productive, reproductive and health information was recorded in the VAMPP Bovino 3.0. Association analyses done, to establish relationships between βHBA concentration and indexes of interest, indicated that Jersey animals suffering clinical hypocalcemia had 3.63 times a chance to have βHBA concentrations over 1.4 mmol.l-1, as compared to healthy ones. However, the results suggest that average βHBA concentrations of 0.66 (95% CI: 0.59 to 0.74) at 8±3 DL in Jersey cows and of 0.59 (95% CI: 0, 52-0.65) at 5±3 DL in Holsteins, as well as βHBA average concentrations of 0.91 (95% CI: 0.78 to 1.05) for Jerseys and 0.69 (95% CI: 0.58 to 0.80) for Holsteins at 30±3 DL, did not affect milk production nor reproduction in dairy herds whose feeding was based on intensive use of tropical forages, plus a balanced food at a rate of 2.5 to 3 kg per cow per day (1.9 Mcal ENL.kg-1, 48% starch).